Seminar Kewirausahaan –Yuk Nabung Saham PPGT Nonongan Salu - Marinus Ronal; Elisabet Pali; Althon K Pongtuluran; Jens B Marewa; Stefani Marina Palimbong (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The objectives to be achieved in this activity are to provide outreach to PPGT Klasis Nonongan on how to invest using a trading system, provide a real picture of investment activities in the capital market and provide outreach about the importance of investing in today's digital era and taking advantage of opportunities. The activities of this organization are generally still unfamiliar with the capital market and consider playing shares to be gambling. The total number of participants who took part in this activity was around 20 people